Theory and practice in sustainable planning and design. Planning, Design, Applications. - (:unkn) unknown (Lang, 2020)
Global warming and the resulting climate change affect the cities most. With the decrease of rural areas in recent years, migration to cities has increased. With the rapid migration, an orderly structuring occurred in the cities, and as a result, the quality of the urban environment has started to decrease. In order to mitigate this issue, planners and designers have started to use different approaches to make cities more sustainable and livable. This book contains new theories, approaches and practices that scientists devise for physical planning and design.
Keywords: Nachhaltige Stadtentwicklung; Nachhaltiges Bauen; Traditionelles Bauen; Historisches Gebäude; Energetische Sanierung; Fallbeispiel; Klimaanpassung; Nichtwohngebäude; Wohngebäude; Wohnsiedlung; Öffentlicher Raum; Nutzungswandel; Klimaanpassung; Grüne Infrastruktur; Urban Agriculture